Where are we with understanding of COVID-19? (2020)
Coronavirus disease 2019 caused by SARS-CoV-2 originated from China and spread across every corner of the world. The scientific interest on COVID-19 increased after WHO declared it a pandemic in the early February of 2020. In fact, this pandemic has had a worldwide impact on economy, health, and lifestyle like no other in the last 100 years. SARS-CoV-2 belongs to Coronaviridae family and causes the deadliest clinical manifestations when compared to other viruses in the family. COVID-19 is an emerging zoonotic disease that has resulted in over 383,000 deaths around the world. Scientists are scrambling for ideas to develop treatment and prevention strategies to thwart the disease condition. In this review, we have attempted to summarize the latest information on the virus, disease, prevention, and treatment strategies. The future looks promising.